Implementation of Project-Based Learning in Science Courses in Early Childhood Education - Epritha Kurnia Wati; Linda Dwiyanti (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to determine the effect of implementing project-based learning (PBL) on the science understanding of students majoring in Early Childhood Education Teacher Education (PG PAUD) in the Early Childhood Science course. This study used a quasi-experimental method with a nonequivalent control group design. The subjects were third-semester PG PAUD students divided into an experimental class and a control class. Data collection techniques used a science concept understanding test and student activity observation sheets. Data were analyzed using descriptive and inferential statistical tests. The results showed that there was a significant difference between the science understanding of students who participated in project-based learning and students who participated in conventional learning. Project-based learning was proven effective in improving the understanding of science concepts and critical thinking skills of PG PAUD students.